Complete genome sequence of an overattenuated highly pathogenic porcine reproductive and respiratory syndrome virus - Wu, Jiajun; Chen, Nanhua; Han, Wei; Cao, Zhen; Deng, Xiaoyu; Wang, Lilin; Yu, Xiuling; Zhou, Zhi; Li, Xiangdong; Shi, Jishu N.; Tian, Kegong (My University, 2012)
JXA1-P170 is an overattenuated highly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV) that has been passaged in vitro 170 times. Vaccination with JXA1-P170 cannot protect pigs against JXA1 challenge. Compared with the parental virus JXA1, JXA1-P170 contains 1 nucleotide (nt) deletion and 113 nt mutations leading to 59 amino acid substitutions. Here we announce the first complete genome sequence of the overattenuated HP-PRRSV.
Keywords: Complete genome sequence; JXA1-P170; Highly pathogenic porcine reproductive and respiratory syndrome virus